Una aproximación a los convenios arbitrales asimétricos: intuiciones sobre su tratamiento legal en el Perú - Dannon Alva, Augusto (2020)
In this paper, the author explores the discussion surrounding the validity of asymmetric arbitration agreements and examines the bases for their treatment in Peru. In several jurisdictions, these agreements are considered as an expression of the contractual freedom of the parties that allows them to design the means to solve their controversies. However, others prohibit it as it poses one of the parties in a disadvantageous situation. Faced with this dilemma, the author seeks to determine the compatibility of these agreements with the Peruvian legal system through the study of various issues emerged around them: consent, inevitability, equality, voidance, pathology, among others.The author seeks to reach an intuitive answer about the validity of asymmetric arbitration agreements, based on the scarce Peruvian legal dispositions, the foundations of arbitration and arbitration agreements and the arguments discussed both in favor and against by compared doctrine and jurisprudence.